Influência de variáveis dendrométricas, anatômicas e ambientais na produção de frutos e sementes de Bertholletia excelsa H.B.K. - Ivanov, Guilherme Boeira (2011)
Bertholletia excelsa H.B.K. is a semi-deciduous species, heliophyle, characteristic of forest land and usually emerging, which collects on the fruits and seeds for use in feed. However, knowledge about the factors that influence the production of the trees is weak. This work aimed to evaluate the influence of rainfall, soil (texture, depth and hydromorphic) dendrometric variables (diameter at breast height and insertion of the crown, tapering, coefficient of taper artificially and taper artificially), qualitative variables (canopy shape and position), competition, sapwood area and size classes and grouping of vessels in the production of fruits and seeds of the species. It was observed that the same number of fruit generate seed yields in kg with significant differences. Rainfall for the month of September shows a positive correlation with the production. The deep soil and with texture sandy clay loam or sandy-clay have a higher yield potential than the shallow and clayey. Trees with less taper (more cylindrical) tended to produce more than trees with greater taper (more conical). Trees with full crowns (circular and irregular) have the same productive potential, and in turn greater potential than those who had half crown. The expected maximum sapwood area decreases exponentially with increasing competition. Trees with sapwood area less than 0.030 m² were not productive and less than 0,075 m² always produce less than 5 kg. Trees that have large solitary vessels are more abundant and have a tendency to produce less than those of other classes. The greatest production potential is expected to trees growing and deep soil, with texture sandy clay loam or clay-sandy, with complete canopies in areas subject to competition for Bertholletia index (IB) below 33, with sapwood area between 0.37450 and 0.29961 square meters and preferably not have large solitary vessels. The proposed model for prediction of seed fresh weight (kg) is Peso=-11.16+0.103636·PPSet +11.699216·galb in soils with texture clayey, in soils with texture sandy clay loam or sandy-clay are level difference with an increase of 7.40 kg of seeds per tree.